Digital Economic Dynamics Innovations, Networks and Regulations - Welfens, Paul J.J.; Weske, Mathias; SpringerLink (Online service) (Berlin, Heidelberg : Springer Berlin Heidelberg : Imprint: Springer, 2007)
The 21st century is increasingly shaped by the expansion of software applications and digital networking. This book analyzes the dynamics and impacts of software development and discusses new institutional and economic changes in the context of digital market economies. Regulatory approaches in OECD countries are compared and country studies evaluated with respect to innovation and welfare aspects. The book furthermore examines telecommunications regulation of fixed line networks, cable TV and mobile communications. There is also focus on the role of EU framework regulation and issues of market power as well as Schumpeterian dynamics.
Software Development Dynamics: Current Trends and Future Developments -- Digital Social Market Economy — Towards a New Economic System -- Market Analyses under the New European Communications Framework - Some Conceptual Issues -- Liberalisation of Telecommunications and Innovation Dynamics in Denmark -- Regulations of Telecommunications and Market Dynamics in Germany -- Innovation in the European and Japanese Mobile Telecommunications Industry -- Collective Dominance, Market Analysis and the 2002 EU Framework Directive: The Case of Mobile Access and Call Origination in Ireland -- Credible Threats as an Instrument of Regulation for Network Industries -- Information Society 2015: Towards Increased Participation.
Keywords: Economic policy; Industrial management; Industrial organization; Economic Policy; Media Management; Industrial Organization